The Effect Of Work Life Balance On Workplace Well-Being Of Employees Of PT. Perdana Inti Sawit Perkasa - Ginting, Kartika Estevania C.; Butarbutar, Freddy; Brahmana, Karina M. (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to analyze the effect of Work-Life Balance on Workplace Well-Being among employees of PT Perdana Inti Sawit Perkasa. Work-Life Balance refers to the balance between work and personal life that can affect employee well-being in the workplace. Workplace Well-Being reflects the level of satisfaction, mental health, and organizational support perceived by employees in the work environment. This study uses a quantitative method with a survey approach, involving 31 respondents consisting of permanent and contract employees at PT Perdana Inti Sawit Perkasa. Data were collected through online questionnaires and analyzed using a simple linear regression test. The results of the study indicate that there is a significant influence between Work-Life Balance on Workplace Well-Being. Employees who have a good balance between work and personal life tend to have a higher level of well-being in the workplace. This study explains the importance of companies in implementing work flexibility policies, organizational support, and a conducive work environment to improve employee well-being. That way, companies can increase employee productivity and loyalty in the long term. The results of this study indicate that organizations, especially in a Limited Liability Company (PT), show a significant relationship between work-life balance and well-being in the workplace. PT Perdana Inti Sawit Perkasa should prioritize initiatives in promoting a healthy balance between work and personal life responsibilities to increase employee satisfaction and productivity.